Preparation of 9.5/65/35 PLZT powders by organic precursor method - Stojanovic, B. D. [UNESP]; Zaghete, M. A. [UNESP]; Cavalheiro, A. A. [UNESP]; Paiva-Santos, C. O. [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications, 2001)
In this study the preparation of 9.5/65/35 PLZT ceramic powders were investigated. The powders with the formula Pb0.905La0.095(Zr0.65 Ti0.35)0.976O3 + 3.5 w% PbO were prepared using Pechini process and partial oxalate method. The powder phase formation, powder morphology, and green density of PLZT were shown.
Keywords: Ceramic materials; Crystal structure; Decomposition; Density (specific gravity); Heat treatment; Morphology; Phase transitions; Positive ions; Powders; Resins; Solutions; Synthesis (chemical); Green density; Lead lanthanium zirconate titanate; Organic precursor method; Partial oxalate method; Pechini process; Lead compounds